2023
DOI: 10.21929/abavet2023.11
|View full text |Cite
|
Sign up to set email alerts
|

Semioquímicos asociados al seguimiento de rastros de hormigas (Hymenoptera: Formicidae): una revisión sistemática

Abstract: Las hormigas son himenópteros muy diversos y de amplia distribución geográfica. Son insectos sociales y su comunicación se basa en señales químicas. Dentro del grupo de semioquímicos que regulan la búsqueda de alimentos están las feromonas de rastro en los caminos. El propósito de esta revisión es documentar las principales feromonas de seguimiento en los senderos que guían a las hormigas hacia las fuentes de alimentación. Se realizó una revisión sistemática basada en las directrices de la declaratoria PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In this study, the following compounds were identified in the habitat: mainly saturated hydrocarbons, aldehydes, and alcohols, and, in a lower proportion, esters, ethers, ketones, terpenes, aromatic compounds, amines, and phenols. Gordon (2021), Jaffé (2004), Kaspari (2003), and other authors have previously established that the following pheromones regulate most of the life of ants: acetates, aldehydes, alcohols, alkanes, and ketones (Cantúa-Ayala et al, 2019;Cruz-Labana et al, 2023). Paterson and Adams (2022) have determined that alkanes are the main components of the tracking, warning, and sexual pheromones of family Formicidae.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the following compounds were identified in the habitat: mainly saturated hydrocarbons, aldehydes, and alcohols, and, in a lower proportion, esters, ethers, ketones, terpenes, aromatic compounds, amines, and phenols. Gordon (2021), Jaffé (2004), Kaspari (2003), and other authors have previously established that the following pheromones regulate most of the life of ants: acetates, aldehydes, alcohols, alkanes, and ketones (Cantúa-Ayala et al, 2019;Cruz-Labana et al, 2023). Paterson and Adams (2022) have determined that alkanes are the main components of the tracking, warning, and sexual pheromones of family Formicidae.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, L. apiculatum must adapt to weather variations when they forage seeking sources of food. The intensity and concentration of foraging pheromones depend on the source of food (Cruz-Labana et al, 2023). Therefore, the semiochemical role of the VOCs found in the external environment (i.e., the foraging sites of L. apiculatum) are determinant in the escamol production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations